2013
DOI: 10.1007/s10856-013-4976-4
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced effect of surface microstructured porous titanium on adhesion and osteoblastic differentiation of mesenchymal stem cells

Abstract: Porous titanium with appropriate surface treatments can be osteoinductive. To investigate the effect of surface treatments of porous titanium on the attachment and differentiation of mesenchymal stem cells (MSCs), two kinds of surface microstructured porous titaniums, H₂O₂/TaCl₅ treated one (HTPT), and H₂O₂/TaCl₅ and subsequent simulated body fluid (SBF) treated one (STPT) were fabricated, and non-treated one (NTPT) was used as control. The morphology, specific surface area (SSA), pore distribution and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…EDX studies of the surface area of the generated microstructures revealed an occasionally altered composition due to the vaporized aluminum of the TiAl 6 V 4 alloy (Figures 3 and 4). The fact that cell adhesion is dependent on both material composition and topography was already investigated by other research groups [13,25,37,38]. Therefore, the results of this study show that the electron beam texturing process for generating microstructures on titanium alloys can be even more attractive due to the lower amount of aluminum found in contact with the cells.…”
Section: Discussionsupporting
confidence: 56%
“…EDX studies of the surface area of the generated microstructures revealed an occasionally altered composition due to the vaporized aluminum of the TiAl 6 V 4 alloy (Figures 3 and 4). The fact that cell adhesion is dependent on both material composition and topography was already investigated by other research groups [13,25,37,38]. Therefore, the results of this study show that the electron beam texturing process for generating microstructures on titanium alloys can be even more attractive due to the lower amount of aluminum found in contact with the cells.…”
Section: Discussionsupporting
confidence: 56%
“…Generally accepted, porous structured Ti alloys have their utilities in osteoinduction of biomaterials4567. They are suitable for repairing / replacing bone defections.…”
mentioning
confidence: 99%
“…This benefits the healing potential of bone growth into the implant91011. Also, based on the in-vitro studies giving a critical support for the osteoinduction of porous Ti, mesenchymal stem cells differentiation towards osteoblasts is promoted with the micro-structured material45. Among all these studies, pore size is a decisive factor to influence the bioactivities at the porous structure during the bone tissue regeneration.…”
mentioning
confidence: 99%
“…The surface roughness and morphology are recognised to improve cell attachment and promote osteointegration [4]. However, simply increasing the roughness with acid etching has shown little improvement in performance in vivo [6,7]. On the other hand, changing the surface chemistry using biocompatible coating materials such as hydroxyapatite (HA), which is similar in composition to the mineral component of bone, can improve osteointegration.…”
Section: Introductionmentioning
confidence: 99%
“…The high temperature followed by rapid cooling can lead to dehydroxylation of HA, change of crystallinity and formation of an amorphous calcium phosphate as well as micro-cracks [4,9]. Despite these drawbacks, plasma spraying coating offers a high throughput method of depositing ceramic coatings on metal implants [4][5][6][7][8][9]16].…”
Section: Introductionmentioning
confidence: 99%